2006
DOI: 10.1007/bf02931584
|View full text |Cite
|
Sign up to set email alerts
|

The dose-dependent H2O2 stress response promotes increased survival forSchizosaccharomyces pombe cells expressing HIV-1 Vpr

Abstract: Human immunodeficiency virus type 1 (HIV-1) viral protein R (Vpr) exerts multiple effects on viral and host cellular activities during infection, including induction of the cell cycle G2 arrest, and cell death in both human cells and the fission yeast Schizosaccharomyces pombe. We show that treament of exponential-phase wild-type Vpr-expressing S. pombe cells with a low, subinhibitory concentration (0.15 mmol/L) of hydrogen peroxide and 0.1 mmol/L thiamine significantly increased both cell proliferation and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…These data are in agreement with earlier observations [3,32]. For comparison, the multiplication of the mutant F341Vpr-expressing cells stopped at 20 h and started again at 26 h [28].…”
Section: Nl4-3vpr Expression-induced Growth Inhibition Cell Cycle G2supporting
confidence: 93%
See 3 more Smart Citations
“…These data are in agreement with earlier observations [3,32]. For comparison, the multiplication of the mutant F341Vpr-expressing cells stopped at 20 h and started again at 26 h [28].…”
Section: Nl4-3vpr Expression-induced Growth Inhibition Cell Cycle G2supporting
confidence: 93%
“…For comparison, the multiplication of the mutant F341Vpr-expressing cells stopped at 20 h and started again at 26 h [28]. Table 2 It has been demonstrated previously that the expression of wild-type NL4-3Vpr in S. pombe induces elongated cells that are delayed or arrested at the G2/M cell cycle transition [3,29,30]. The G2 arrest mediated by Vpr utilizes the cellular signaling pathway whose physiological function is to recognize replication stress and which is strongly associated with the oxido-reduction balance of cells [33].…”
Section: Nl4-3vpr Expression-induced Growth Inhibition Cell Cycle G2mentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to Tat, HIV-1 gp120 protein has been shown to cause reactive oxygen species (ROS) production in glial cells leading to neurodegeneration and apoptosis (10). Finally, in a recent study, HIV-1 Vpr protein was shown to be involved in OS pathway (11).…”
mentioning
confidence: 99%